Actions and feelings in sync: exploring the relationship between synchrony and empathy in children’s dyadic musical interactions - Tzanaki, Persefoni; Eerola, Tuomas; Timmers, Renee (Frontiers in Psychology, 2025)
IntroductionThis study investigated the relationship between interpersonal synchrony and empathy in children’s music-making. Drawing from a theoretical framework that suggests a bidirectional relationship between synchrony and empathy, the study examined three key aspects of this relationship: (1) the role of children’s trait empathy in achieving interpersonal synchrony; (2) synchrony’s effects on empathy following brief musical interactions; and (3) the role of experimentally induced empathy in moderating the social bonding effects of synchrony.MethodsSeventy-two pairs of primary school children participated in two experiments. The first involved free tapping, where participants were instructed to synchronize with one another. In the second experiment, synchrony was manipulated, using an apparatus that either facilitated or disrupted synchrony within pairs. Prior to this task, half of the pairs received a false message about their partner, intended to induce empathy. Trait empathy and social bonding were assessed via self-reported questionnaires.ResultsFindings revealed that cognitive and affective trait empathy related to children’s ability to synchronize with one another, particularly when participants’ temporal performance was unstable (Aspect 1). In addition, brief synchronous musical interactions were found to promote empathy within pairs (Aspect 2). Our method to experimentally induce empathy was not sufficient to influence the social bonding effects of synchrony (Aspect 3). However, trait empathy, pairs’ gender composition and familiarity between children emerged as factors affecting the attainment of synchrony and the bonding experience of music-making.DiscussionThis is the first empirical study investigating multiple aspects of the interplay between synchronizing and empathizing in children, paving the way for future exploration of the mechanisms allowing for a bidirectional relationship. The study outcomes can inform musical interventions leveraging this relationship to nurture children’s simultaneous musical and social development.